Aerosol chemical characterization and role of carbonaceous aerosol on radiative effect over Varanasi in central Indo-Gangetic Plain. (January 2016) - Tiwari, S.; Dumka, U.C.; Kaskaoutis, D.G.; Ram, Kirpa; Panicker, A.S.; Srivastava, M.K.; Tiwari, Shani; Attri, S.D.; Soni, V.K.; Pandey, A.K.
Abstract: This study investigates the chemical composition of PM10 aerosols at Varanasi, in the central Indo-Gangetic Plain (IGP) during April to July 2011, with emphasis on examining the contribution of elemental carbon (EC) to the estimates of direct aerosol radiative effect (DARE). PM10 samples are analysed for carbonaceous aerosols (Organic Carbon, OC and EC) and water-soluble ionic species (WSIS: Cl −, SO4 2−, NO3 −, PO4 2− NH4 +, Na +, K +, Mg 2+ and Ca 2+ ) and several diagnostic ratios (OC/EC, K + /EC, etc) have been also used for studying the aerosol sources at Varanasi. PM10 mass concentration varies between 53 and 310 μg m −3 (mean of 168 ± 73 μg m −3 ), which is much higher than the National and International air quality standards. The OC mass concentration varies from 6 μg m −3 to 24 μg m −3 (mean of 12 ± 5 μg m −3 ; 7% of PM10 mass), whereas EC ranges between 1.0 and 14.3 μg m −3 (4.4 ± 3.9 μg m −3 ; ∼3% of PM10 mass). The relative low OC/EC of 3.9 ± 2.0 and strong correlation (R 2 = 0.82) between them suggest the dominance of primary carbonaceous aerosols. The contribution of WSIS to PM10 is found to be ∼12%, out of which ∼57% and 43% are anions and cations, respectively. The composite DARE estimates via SBDART model reveal significant radiative effect and atmospheric heating rates (0.9–2.3 K day −1 ). Although the EC contributes only ∼3% to the PM10 mass, its contribution to the surface and atmospheric forcing is significantly high (37–63% and 54–77%, respectively), thus playing a major role in climate implications over Varanasi. Highlights: Carbonaceous aerosols account for 14% (6%–26%) of PM10 mass at Varanasi. Relatively lower OC/EC suggests higher contribution from fossil-fuel combustion. Relatively low secondary organic aerosol formation. Ratios between organic and inorganic species help in understanding aerosol source. EC contributes to the surface (37–63%) and atmospheric (54–77%) radiative effect.